Secondary Distribution of HIV Self-Testing Kits to Social and Sexual Networks of PLWH in KwaZulu-Natal, South Africa. A Brief Report - Nsika Sithole (Frontiers in Public Health, 2022)
BackgroundTo reach 95% of persons living with HIV (PLWH) knowing their HIV status, alternative testing approaches such as HIV self-testing (HIVST) and secondary HIVST kit distribution are needed. We investigated if secondary HIVST kit distribution from male and female PLWH in South Africa would successfully lead to their contacts testing for HIV and linking to care if positive.MethodsMale and female PLWH participating in an HIV treatment trial between July and November 2018 in KwaZulu-Natal, South Africa were offered participation as “HIVST kit distributors” in a pilot of secondary distribution of HIVST kits to give to sexual partners and social networks. Univariate descriptive statistics were used to describe the characteristics of volunteer distributors, proportion of HIVST recipients who reported their results, and linkage to care among those who tested positive using HIVST were assessed.ResultsSixty-three participant kit distributors accepted kits to disperse to contacts, of whom 52% were female, median age was 34 years (IQR 26-42.5), 84% reported 1 sexual partner and 76% did not know their partner's HIV status. HIVST kit distributors took 218 kits, with 13/218 (6%) of kits reported to be intended to be given to a sexual partner. A total of 143 HIVST recipients reported their HIVST results; 92% reported their results were negative, 11 recipients reported positive results and 1 HIVST-positive recipient was linked to HIV care.ConclusionSecondary distribution of HIVST to social networks and sexual partners from South African PLWH is feasible, with two thirds of contacts reporting use of the HIVST kits. Additional support is necessary to facilitate linkage to care.